Natural Resources Product Prospects-International Conference on Fluids and Chemical Engineering-FluidChE 2017, Malaysia - Jolius, Gimbun; Gajendran, Natarajan; Ranganathan, Balu (Informatics Publishing Limited, 2017)
The 2nd edition of Fluids and Chemical Engineering conference, FluidsChE 2017 held in April 2017 at Kota Kinabalu, Sabah is organised by the Center of Excellence for Advanced Research in Fluid Flow (CARIFF) Universiti Malaysia Pahang, Malaysia. FluidsChE 2017 covers a wide area of engineering and sciences with the theme "Advancing Fluids Engineering for A Sustainable Future". Over 200 submissions were received from countries such as India, Iraq, Pakistan, Indonesia, Malaysia, Thailand, Kazakhstan and Qatar. More than 100 full papers were submitted for the special issue. After an extensive peer-review process, 66 papers were finally selected for publication. The current special issue volume consisted of natural resources product lifecycle, polymer technology and pharmaceutical technology.